THE CONCEPTUAL BASES OF TOURIST CLUSTER FORMATION FOR DEVELOPMENT OF NEWLY FORMED UNITED TERRITORIAL COMMUNITY - Kropelnytska , S.O.; Perederko, V.P. (The actual problems of regional economy development, 2016)
Thе article is devoted to the problems of united territorial communities (UTC) development and outlining their possible solutions. One of the goals of UTC defined formation tourist cluster. The results is to identify tourism resources, tourism infrastructure formation of Pechenizhenska UTC. The novelty – the conceptual foundations for creating a tourist cluster in the region at the tourism infrastructure of newly UTC established. The practical significance is reduced to provide specific proposals to build a tourism cluster algorithm and application project approach at its creation. JEL: M 20